OVERVIEW OF FACTORS THAT AFFECT THE UTILIZATION OF HEALTH CENTER LIU DISTRICT SABBANGPARU WAJO REGENCY - Irma Dwianty (Sean Institute, 2021)
Health care is one of the determinants of public health degrees. One of the targets is the Center for Public Health (Puskesmas). Puskesmas is a functional unit that is a center for public health development that also fosters community participation in addition to providing comprehensive and integrated services to the community in its work area in the form of basic activities. According to the Wajo district health office, LIU health center is a health center that has the lowest number of kunjugan compared to other health centers in Wajo regency. The lack of utilization of health services in LIU Health Center is the background of the author doing this study. The purpose of this study is to find out the picture of factors that affect the utilization of LIU health centers based on community knowledge and the distance of community residence with health centers. The type of research used is a descriptive survey. How to take samples is done with purposifve sampling technique. Based on the results of the study obtained that showed that of 50 respondents (44.7%) who use health centers, who have enough knowledge as many as 35 respondents (31.3%) and who have less knowledge as many as 15 respondents (13.4%) while of 62 respondents (55.3%) who do not use health centers, there are 25 respondents (22.3%) who have enough knowledge and who have less knowledge as many as 37 respondents (33.0%). Meanwhile, of the 50 respondents (44.7%) utilizing health centers that have a close residence distance to the health center as many as 33 respondents (29.5%) and those who have a distance of residence far from the health center as many as 17 respondents (15.2%) while those who do not use the health center as many as 62 respondents (55.3%) who have a close residence distance to the health center as many as 25 respondents (22.3%) and who have a distance of residence with the health center as many as 37 respondents (33.0%). Therefore it can be concluded that there is a relationship between knowledge and the utilization of Liu's health center. From the results of the study also found that there is a relationship between the distance of the community and the utilization of puskesmas.